2021
DOI: 10.1038/s41467-021-22796-8
|View full text |Cite
|
Sign up to set email alerts
|

Efferent feedback controls bilateral auditory spontaneous activity

Abstract: In the developing auditory system, spontaneous activity generated in the cochleae propagates into the central nervous system to promote circuit formation. The effects of peripheral firing patterns on spontaneous activity in the central auditory system are not well understood. Here, we describe wide-spread bilateral coupling of spontaneous activity that coincides with the period of transient efferent modulation of inner hair cells from the brainstem medial olivocochlear system. Knocking out α9/α10 nicotinic ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Action potential bursts generated in SGNs propagate along the ascending auditory pathway with remarkable fidelity, inducing correlated firing of neurons within isofrequency zones in central auditory centers 21, 22, 46 . In the inferior colliculus (IC), this peripheral input manifests as discrete bands of neuronal activity aligned to the future tonotopic axis 22, 47 . To determine if the correlated firing of auditory neurons within these lamina is affected in Cx26 cKO mice, we performed widefield neuronal calcium imaging in awake, unanesthetized mice ( Gjb2 fl/fl ; Snap25-T2A-GCaMP6s and Tecta-Cre;Gjb2 fl/fl ; Snap25-T2A-GCaMP6s ) through a cranial window placed over the midbrain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Action potential bursts generated in SGNs propagate along the ascending auditory pathway with remarkable fidelity, inducing correlated firing of neurons within isofrequency zones in central auditory centers 21, 22, 46 . In the inferior colliculus (IC), this peripheral input manifests as discrete bands of neuronal activity aligned to the future tonotopic axis 22, 47 . To determine if the correlated firing of auditory neurons within these lamina is affected in Cx26 cKO mice, we performed widefield neuronal calcium imaging in awake, unanesthetized mice ( Gjb2 fl/fl ; Snap25-T2A-GCaMP6s and Tecta-Cre;Gjb2 fl/fl ; Snap25-T2A-GCaMP6s ) through a cranial window placed over the midbrain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the precise borders of the different nuclei of the IC have been disputed based on different classifications ( Meininger et al, 1986 ; Coote and Rees, 2008 ; Grana et al, 2017 ; Gay et al, 2018 ), the ICD and ICX neurons have been less examined than ICC neurons in past studies. However, recent studies using two-photo imaging have greatly expanded the knowledge of the physiological properties of the dorsal surface of the IC ( Geis et al, 2011 ; Geis and Borst, 2013a ; Geis and Borst, 2013b ; Ito et al, 2014 ; Barnstedt et al, 2015 ; Chen and Song, 2019 ; Wong and Borst, 2019 ; Wang et al, 2021 ). More detailed spatial tonotopic gradients and electrophysiological properties were confirmed in the dorsal IC, refuting claims that the ICD lacks topographic organization or is simply an extension of the ICC ( Willott, 2001 ; Malmierca et al, 2008 ; Lumani and Zhang, 2010 ; Barnstedt et al, 2015 ; Wong and Borst, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Morley et al (2017) have used constitutive α9 and/or α10 KO mice to show that only the doubly constitutive mice showed abnormal efferent innervation of cochlear hair cells. Moreover, a very recent study (Wang et al, 2021) has demonstrated that, in the developing auditory system, α9 and α10-containing receptors are involved in the spontaneous activity generated in the cochleae that propagates to the CNS to promote circuit formation.…”
Section: Structure Pharmacology and Localization Of α9 Nachrsmentioning
confidence: 99%